2018
DOI: 10.1089/biores.2018.0007
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Acceptance of Human Papillomavirus Vaccine for Cervical Cancer Prevention Among Urban Professional Women in Bangladesh: A Mixed Method Study

Abstract: Prophylactic human papillomavirus (HPV) vaccination is the most effective preventive method against invasive cervical cancer, the second leading cause of cancer-related deaths among women in Bangladesh. Evidence on women's knowledge and perception about cervical cancer and HPV vaccination are needed for effective implementation of national cervical cancer prevention programs. The objective of this study was to assess the knowledge, attitude, and acceptance of cervical cancer, HPV, and HPV vaccination among urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
3
5
5
Order By: Relevance
“…The findings of this study reported that more than 6 out of every 10 participants were aware of HPV ( Table 2). The level of awareness among university students of this study was higher than the level of awareness (56.6%) among urban women in Bangladesh 12 . It was expected since the study was conducted among university students.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The findings of this study reported that more than 6 out of every 10 participants were aware of HPV ( Table 2). The level of awareness among university students of this study was higher than the level of awareness (56.6%) among urban women in Bangladesh 12 . It was expected since the study was conducted among university students.…”
Section: Discussioncontrasting
confidence: 75%
“…Understanding people's knowledge and attitude towards HPV infection and vaccination may facilitate to design of effective strategies and interventions in raising awareness and encouraging the uptake of the vaccine among the target population. Previous studies on knowledge and attitudes towards HPV infection and vaccination has focused on women in Bangladesh 11,12 . However, there is a lack of research that explores young adult's knowledge and attitude towards HPV infection and vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…A mixed-method study was conducted in Dhaka, Bangladesh in December 2013 among professional women employed by private banks. It revealed that only 26% of the participants had heard about cervical cancer and 56.6% of them had heard about HPV vaccination [12]. In the present study, 83.3% of people knew that PAP smear test detects cervical cancer even before the symptoms appear, which were in comparison with similar studies [13][14][15].…”
Section: Discussioncontrasting
confidence: 44%
“…Researchers report a general lack of awareness about HPV and the availability and need for the HPV vaccine [40][41][42][43]. Furthermore, they report an association between the participant's gender [44] and age [45,46] and the likelihood to initiate HPV vaccination, with females more likely than males to report a willingness to initiate and complete HPV vaccination [44,47]. In our study, perceived beliefs that HPV causes cancer, that HPV vaccination is effective in preventing cancer, and that HPV vaccination is effective in adolescents' early years were significantly associated with the initiation and completing of HPV vaccination; findings consistent with the previous research [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%